Patch Time Allocation and Oviposition Behavior in Response to Patch Quality and the Presence of a Generalist Predator in Meteorus pulchricornis (Hymenoptera: Braconidae). Issue 1 (4th May 2015) - Sheng, Sheng; Ling, Meng; Fu-an, Wu; Baoping, Li
Abstract : Foraging parasitoids often must estimate local risk of predation just as they must estimate local patch value. Here, we investigate the effects a generalist predator Chlaenius bioculatus (Coleoptera: Carabidae), has on the oviposition behavior and the patch residence decisions of a solitary parasitoid Meteorus pulchricornis (Hymenoptera: Braconidae) in response to the varying host quality of Spodoptera litura (Lepidoptera: Noctuidae) larvae (L2 and L4). M. pulchricornis attacked more L4 than on L2 hosts, with the difference in attack rate varying depending on predation treatments, greater in the presence (either actively feeding or not) of the predator than in the absence of it. The parasitoid attacked fewer L2 and L4 hosts when the predator was actively feeding than when it was not feeding or not present in the patch. M. pulchricornis decreased the patch leaving tendency with increasing rejections of hosts, but increased the tendency in response to the presence of the predator as compared with the absence of it, and furthermore, increased the patch leaving tendency when the predator was actively feeding as compared with when it was not. Our study suggests that M. pulchricornis can exploit high quality patches while minimizing predation risk, by attacking more hosts in high quality patches while reducing total patch time in response to risk of predation.